Histologic and histomorphometric evaluation of the bone regeneration following cortical bone repositioning in a rabbit mandible. (23rd April 2019) - Martinez‐de la Cruz, Gerardo; Yamauchi, Kensuke; Odajima, Kenji; Kataoka, Yoshihiro; Nogami, Shinnosuke; Takahashi, Tetsu
Abstract: Background: Although bone graft (BG) is the gold standard for bone augmentation, its use is hampered by donor site morbidity and limited quantity. Purpose: To evaluate the capabilities of bone formation by cortical bone repositioning (CBR) as the healing response following grafting of autogenous bone block without filling biomaterial at the gap between gap and recipient. Materials and Methods: Twelve Japanese White rabbits were divided into three groups (postoperative 2, 5, and 8 weeks). A cortical block was freed from the mandibular body, half of the block was positioned and fixed overlapped the original bone surface beside the defect and the other half remained only elevated above the defect. Three areas were decided for the evaluation; BG, CBR, and defect (D) area. Areas were evaluated by micro‐CT, histology, and histomorphometric analysis. Results: There is no statistical difference between BG and CBR by evaluating distance and area in histomorphometrical analysis ( P < .05). D area showed statistical decrease compared with BG and CBR at week 2. Histologically, new bone was evident at week 2, mature bone was observed in all three areas at week 8, D area disappeared and fused completely with the elevated bone block. Conclusion: CBR has potential for bone augmentation as BG induced from its own regenerative ability of healing process.